Development of Biodegradable, Cellulose-Based, Essential Oil and Chitosan Drug Delivery Systems for Cosmetic Mask Applications - Moreira, Joana; Lopes, Catarina; Lis Arias, Manuel-José; Silva, Lúcia; Curto, Joana (KnE Materials Science, 2022)
The goal of this research was the development of cellulose-based biodegradable drug delivery systems solutions for cosmetic mask applications. Cellulose-based materials derived from natural renewable sources provide a sustainable alternative to nonwoven cosmetic masks derived from nondegradable fossil-based raw materials. An experimental design was executed to assemble the 3D cellulose fibres matrix and the water in oil emulsion comprising the active molecules from Mentha piperita L. Two types of biopolymeric additives were used, one derived from a nano/micro fibrillated cellulose pulp and another one including chitosan. A 3D computational simulation study was performed to enhance porosity and strength properties. The results indicated that the cosmetic face mask optimized prototypes, made from a biodegradable 3D matrix of cellulose fibres and active molecules, are suitable for dermic use. Keywords: biopolymers, dermic application, drug delivery systems (DDS), essential oil, Mentha piperita